What Counts as Internationalization and for Whom: Comprehensive Internationalization at Historically Black Colleges and Universities (Comparative & International Education Series, 2021)
This chapter explores the issue of what counts as internationalization at HBCUs in terms of the elements of comprehensive internationalization articulated by the American Council on Education.  It acknowledges the variations in engagement with internationalization at HBCUs and the difficulties, including financing, that have exacerbated the challenges they face. The chapter argues that comprehensive internationalization is the only strategy that will allow these institutions to respond to the exacting and unyielding forces of globalization and it offers multiple examples of strategic engagement in this work that are both affordable and productive. The chapter challenges HBCUs to reckon with the indispensability of internationalization by making it a core priority in their strategic-planning processes.